Characteristic Of Silicified Coal On Tanjung Agung Syncline, Muara Enim, And It’s Effect Due The Mining Industry - Fandi Fadliansyah (Politeknik Akamigas Palembang, 2017)
The presence of silicified coal characterized several coal seam in Muara Enim Formation and become the important issue in coal mining industry. Silicified coal found in the South of Tanjung Agung District, Muara Enim Regency, South Sumatra. The occurence of silica presume related to the volcanic activity during the late miocene along the regression phase that affected the sedimentation process of Muara Enim Formation. Tuffaceous sandstone layer can possibly recognized as the main source of the silica. Aquisition data process done by observing the research area and several previous study. Sampels used were taken from several coal outcrop. Petrography analysis used to explain the characteristic of silicified coal microscopically and used to analyze the possibility of its genesis. The presence of silicified coal characterized the coal seam occur in southern limb of Tanjung Agung Syncline that distinguish it with the coal seam on northern limb. Macroscophically, silicified coal found generally blackish gray color, hard, in the form of lenses and layering and microscophically mostly dominated by crystal quartz in the form of detrital and diagenetic silica. Silicified coal may cause problems in coal mining activity. Particular treatment should be applied during the mining activity because of its hardness.